Challenges of Implementing Reverse Logistics in Small and Medium Enterprises (SMEs) - Al-Huzaili, Sami Ahmed Faraj; Mokhtar, Ahmad Irdha Bin; Muhamat, Madya Razaleigh Bin (ExcelingTech, 2025)
Reverse coordination is an essential component of sustainable supply chain management, enabling businesses to recover value from returned products while minimizing environmental impact. While large corporations have increasingly integrated reverse coordination into their operations, small and medium enterprises (SMEs) often face considerable barriers that hinder implementation. This study explores the key challenges SMEs encounter in adopting reverse coordination, using a qualitative methodology that combines secondary data analysis with semi-structured interviews conducted with logistics managers from ten SMEs across diverse sectors.The findings reveal six primary obstacles: financial constraints, lack of technical expertise, inadequate infrastructure, weak regulatory pressure, low customer awareness, and organizational resistance to change. These barriers are interconnected and reflect both internal limitations and external systemic factors. Despite these challenges, the research underscores the strategic potential of reverse logistics for SMEs, including cost savings, regulatory compliance, improved customer satisfaction, and new revenue opportunities.The study concludes with practical recommendations to support SMEs in overcoming these challenges highlighting the need for government incentives, targeted training, affordable technologies, collaborative logistics networks, and enhanced customer engagement. Addressing these issues through coordinated efforts can help SMEs realize the full value of reverse logistics and contribute to a more circular and sustainable economy.